Pengembangan Multimedia Pembelajaran Interaktif Mata Pelajaran IPA Untuk Siswa Kelas IV SD Negeri 1 NIPA Berbasis Desktop - Ningsih, Intan Apriliani Adi; Susilowati, Dyah; Madani, Miftahul (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2025)
Science learning in elementary schools often struggles with the delivery of abstract concepts and the limited use of interactive media. Observations in a fourth-grade class at SD Negeri 1 Nipa revealed that instruction relied solely on thematic textbooks, resulting in low student engagement and limited understanding of scientific concepts. This study aimed to develop and evaluate the feasibility and effectiveness of a desktop-based interactive multimedia tool to support science learning. Using a Research and Development (R&D) approach, the study applied the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The multimedia was created using Articulate Storyline and Adobe Photoshop, and tested on a small scale with fourth-grade students. Evaluation involved expert validation and student learning assessments. The results of this study showed that the multimedia received an average validation score of 91.32% from three experts, categorized as "highly feasible". Effectiveness testing showed a significant improvement in student performance, with the average score increasing from 58.75 (pre-test) to 87.75 (post-test). The N-Gain score of 0.70 indicated a high level of learning gain, further confirmed by a paired sample t-test result of 0.000 (p < 0.05), showing statistical significance. In conclusion, the desktop-based multimedia is both feasible and effective in enhancing science learning outcomes. It is strongly recommended as an innovative instructional medium to address the challenges of science education at the elementary level.